Ecofisiologia de bromeliaceae de formações periféricas de Mata Atlântica - Favoreto, Fernanda Campanharo (2023)
Functional traits make up the adaptability of species and allow distinguishing ecophysiological strategies of communities. A group of interest in terms of resistance to stress and distribution of ecophysiological traits is the Bromeliaceae family, which traditionally has functional types distinguished by strategies for obtaining water, levels of dependence on soil and/or peltate trichomes and the photosynthetic metabolic route. Bromeliaceae has the Atlantic Forest as one of its centers of diversity. In this domain, this family is of great importance in the peripheral restinga and inselberg formations. The objective of this study was to identify in situ the ecophysiological responses of bromeliads from these formations. In the dry and rainy seasons, 26 photosynthetic, nutritional and morphological leaf traits were analyzed, in addition to traits specific to Bromeliaceae, in communities from three restinga sites and three inselberg sites in the north of Espírito Santo, Brazil. Initially, a comparison was made between the restinga and inselberg communities, between the rainy and dry seasons and between species throughout the entire period. Restingas showed lower photochemical and nutritional performance, especially in the dry season. However, species from both environments do not show a significant drop in the maximum photochemical efficiency of FSII (ᵩP0) in its general average, demonstrating different adaptation strategies to resource limitations. Secondly, a cluster analysis was carried out to verify whether the response patterns followed the functional groups traditionally recognized for the family. The groups formed reflect the history of the adaptive radiation of the lineages, with distinct patterns between species specialized in restinga, specialized in inselbergs and species with a distribution common to Atlantic Forest formations. Finally, modeling was carried out to evaluate the nutritional and morphological basis of chlorophyll a fluorescence traits, which demonstrated that photosynthetic traits, especially the photochemical performance index per absorption center (PIABS), are more responsive to nutritional issues (phosphorus and nitrogen) and water availability. This pattern is partially different from what is expected from the spectrum of leaf economy and varies between the functional groups traditionally recognized for the family. Thus, bromeliads respond physiologically in the peripheral environments of the Atlantic Forest according to their history of adaptive radiation, demonstrating that they are adapted to imitating resources from these environments, even though they are more susceptible to stress in sandbanks and present different photosynthetic strategies. These chlorophyll a fluorescence responses respond most strongly to phosphorus and nitrogen content and available water.